Map of Atlin mining district : compiled from the latest surveys. - Brownlee & Lowry (Atlin, B.C.) (Department of Mines, 1905)
Map shows mines, mineral resources, "mineral claims," roads, trails, mountains, glaciers, divisions, and towns for British Columbia and Northwest Territory; "provisional international boundary" between British Columbia and the United States. Relief shown by hachures and spot heights. Scale [ca. 1:379,000].